Nieuwe vormen en traditionele bouw: het Vleeshuis te Kampen in het midden van de 16de eeuw (Bulletin KNOB, 1994)
The old meat-market 'Oude Vleeshuis', Oudestraat 119, has served as centre of the meat trade in Kampen for over a hundred years, namely from the last quarter of the 15th century until 1593. In 1557 the town council had the building thoroughly renovated. The natural-stone facade dates back to that year. In spite of radical alterations, this facade is still to be rated among the most interesting examples of early-Renaissance facades in The Netherlands.The facade was hewn and built by mason Lambert Stuurman, who during the fifties and sixties of the 16th century made a flourishing career for himself as a mason, but also as a building contractor and a trader in building materials who was international in scope. However, it is not clear whether Lambert Stuurman also designed the facade. No matter who the designer may have been, the design of the facade is by no means a provincial piece of work executed by a mediocre master or a mediocre architect.It is a well-considered design, for which an early Vitruvius edition must have been used as example. A.A. Kok, the restoration architect in 1939, did not have this detailed knowledge at his disposal. At the time of restoration this resulted in heightening the, evidently original, second floor and in applying a gable, modelled after the work of Vredeman de Vries. In 1557 the designer of the facade applied the classical forms in a freer, less experimental way than became customary during late 16th-century Mannerism.In his reconstruction the restoration architect focused on this latter period, and in doing so he was also deceived by a wrong notion of the date of building of the facade. Later Kok probably had his doubts about this dating. Eleven years after the restoration he proposed in an article: 'If it has to be painted over again some day, my advice is to add: ANNO DOMINI 1565; this is not likely to be incorrect by more than five years'. We propose to change this date into 1557.